Creating Effective Teaching and Learning Environments: First Results from TALIS - OECD - OCDE (OCDE, 2018)
Data and research on early childhood and schools, childhood education and care, Programme for International Student Assessment (PISA), Education GPS, Teaching and Learning International Survey (TALIS), This publication is the first report from the International Teaching and Learning Survey (TALIS). It provides quantitative, policy-relevant information on the teaching and learning environment in schools in 24 countries and has a focus on lower secondary education..